2020
DOI: 10.1109/access.2020.2995651
|View full text |Cite
|
Sign up to set email alerts
|

Constant Tension Control of Hybrid Active-Passive Heave Compensator Based on Adaptive Integral Sliding Mode Method

Abstract: Heave compensation systems are of great importance to the safety and efficiency of marine operations subject to irregular-wave excitation. While many efforts have been made to improve the displacement compensation control, only a few of researchers pay their attention on tension compensation control. This paper presents an adaptive robust integral sliding mode control (ARISMC) based on the back-stepping method to realize constant tension control of hybrid active-passive heave compensator (HAHC) applied to heav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…¼ EA (20) According to the above mechanical-structure analysis, in the rewind section, the main mechanical structural factors affecting the yarn tension include the radius of the overfeed roller R i and distances L 1 and L 2 between the overfeed roller and the spindle, These parameters need to be adjusted according to the actual yarn characteristics in production. During the working process of the winding machine, the yarn tension is mainly adjusted by non-mechanical structural factors, such as the speed n 1 of the overfeed roller, the speed n 2 of the spindle, and the speed of the yarn guide.…”
Section: Rewind Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…¼ EA (20) According to the above mechanical-structure analysis, in the rewind section, the main mechanical structural factors affecting the yarn tension include the radius of the overfeed roller R i and distances L 1 and L 2 between the overfeed roller and the spindle, These parameters need to be adjusted according to the actual yarn characteristics in production. During the working process of the winding machine, the yarn tension is mainly adjusted by non-mechanical structural factors, such as the speed n 1 of the overfeed roller, the speed n 2 of the spindle, and the speed of the yarn guide.…”
Section: Rewind Sectionmentioning
confidence: 99%
“…Researchers have proposed many methods on the control algorithm, including fuzzy control, [12][13][14][15][16][17] sliding mode control, [18][19][20] neural networks, [21][22][23][24][25][26] iterative learning, [27][28][29][30][31] etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the reduction in the standard deviation of the rope tension may be up to 50% [8]. Yan et al designed an adaptive robust integral sliding mode control (ARISMC) based on the back-stepping control method strategy to realize constant tension control of hybrid active-passive heave compensator (HAHC) applied to heavy deep-sea towing systems [9]. Sandre-Hernandez et al introduced a PSO algorithm to identify the direct and quadrature stator inductances and the stator resistance of a PMS compensation motor [10], nevertheless, PSO algorithm is prone to find local optima when dealing with parameter optimization.…”
Section: Wave Generation and Ship Motion Coordinatementioning
confidence: 99%
“…The results show that the proposed adaptive robust integral sliding film controller has advantages over the conventional PI controller regarding the accuracy and robustness of tension compensation. 22 From the above, most of the scholar’s research in lift and sink compensation is directed to the study of single reel hydraulic or electric winches and the study of controlled lift and sink displacement. There is little research on the constant tension control of traction winch under heave.…”
Section: Introductionmentioning
confidence: 99%